Security risk analysis of power 5G hybrid networking - Xiaojian ZHANG; Jiaxuan FEI; Haitao JIANG; Qigui YAO (Dianxin kexue)
5G communication technology provides strong support for the power internet of things, and it also introduces new security challenges in the application process of the power industry.Starting from the analysis of the needs of the power 5G business, five 5G networking deployment and construction plans were proposed, and a comparative analysis of them was conducted in security and cost.And then, a hybrid networking architecture of 5G and power communication networks was proposed, and the 5G network slicing architecture was re-segmented according to business scenarios.Finally, from the four parts of terminal access, edge computing, network channel and core network, the security risks introduced by 5G technology were analyzed in detail.